Classification and Rankingskills for Children Enrolled and Not Enrolled in Kindergarten: A Comparative Study (Journal Of Educational and Psychological Researches, 2025)
The current study seek to identify the classification and arrangement skills of children enrolled and not enrolled in kindergarten. The purposes include Classification and ranking skills for first-year primary school students enrolled in kindergarten and Classification and ranking skills for first-year primary school students who are not enrolled in kindergarten, the statistical significance of the differences in classification and ranking skills for first grade primary school students enrolled and not enrolled in kindergarten. The research community included children in the first grade of primary school in the public schools of the six education directorates, including Al-Karkh and Al-Rusafa in Baghdad city. To achieve this, the researcher adopted an integrative framework of theories. He developed a test of classification and arrangement skills according to the practical steps in Constructing the tests and standards consists of (7) vitual items. The test instructions and pictures for each item were prepared according to the scientific instructions for constructing the tests. They were presented to a group of experts, arbitrators, and specialists in kindergartens, measurement, evaluation, psychological sciences, and education, who numbered ( 17) Arbitrator. The test was applied individually to a sample of (300) boys and girls who were selected randomly. The researcher analyzed the test items statistically. The results disclosed that first grade children enrolled in kindergarten have a high level of classification and arrangement skills. First grade children who are not enrolled in kindergarten have a high level of classification and arrangement skills. There are no statistically significant differences in classification and arrangement skills for first grade students enrolled and not enrolled in kindergarten.